Gut microbiota is a potential factor in shaping phenotypic variation in larvae and adults of female bumble bees - Guo, Baodi; Tang, Jiao; Ding, Guiling; Mashilingi, Shibonage K.; Huang, Jiaxing; An, Jiandong (Frontiers in Microbiology, 2023)
Abstract: Host symbionts are often considered an essential part of the host phenotype, influencing host growth and development. Bumble bee is an ideal model for investigating the relationship between microbiota and phenotypes. Variations in life history across bumble bees may influence the community composition of gut microbiota, which in turn influences phenotypes. In this study, we explored gut microbiota from four development stages (early-instar larvae, 1st instar; mid-instar larvae, 5th instar; late-instar larvae, 9th instar; and adults) of workers and queens in the bumble bee Bombus terrestris using the full-length 16S rRNA sequencing technology. The results showed that morphological indices (weight and head capsule) were significantly different between workers and queens from 5th instar larvae (p < 0.01). The alpha and beta diversities of gut microbiota were similar between workers and queens in two groups: early instar and mid instar larvae. However, the alpha diversity was significantly different in late instar larvae or adults. The relative abundance of three main phyla of bacteria (Cyanobacteria, Proteobacteria, and Firmicutes) and two genera (Snodgrassella and Lactobacillus) were significantly different (p < 0.01) between workers and queens in late instar larvae or adults. Also, we found that age significantly affected the microbial alpha diversity as the Shannon and ASVs indices differed significantly among the four development stages. Our study suggests that the 5th instar larval stage can be used to judge the morphology of workers or queens in bumble bees. The key microbes differing in phenotypes may be involved in regulating phenotypic variations.